Programa de participación parental “Mi escuela es importante” y gestión escolar de una I.E. del distrito de Sanagorán-Huamachuco 2018 - Gamboa Domínguez, Leslie Krist (2023)
This study is an experimental research and it was done to determine if the application of the parental program “My school is important” could improve the school management of I.E No. 81725 of Sanagorán – Huamachuco 2018._x000D_ For this research, we worked with a sample of 25 parents of the I.E N° 81725 of Sanagorán-Huamachuco 2018, the hypothesis testing was done with the classic pre- experimental design with pre-test and post-test applied to the experimental group._x000D_ The application of the parental program "My school is important" was carried out based on 12 workshops. These workshops aimed at developing attitudes in parents regarding parental participation in school management to improve learning achievement. For this, the Questionnaire for the Participation of Parents in Primary Schools was used as a data collection instrument._x000D_ As a result, it was obtained that in the pre-test 16% of the participants were at a low level and 84%, at the medium level. Against this, in the post test it was obtained that 12% of the participants were in the middle level and 88% in a high level, added to this, in the Student's T-test a p-value of 0.000 <0.05 significant. Therefore, based on the results obtained, the effectiveness of the application of the parental participation program in the improvement of educational management can be affirmed.